Pathophysiologic similarities between autism spectrum disorder and Alzheimer's disease: therapeutic possibilities - Phillips, William Thomas; Sheesley, Alison P.; Schwartz, Joyce Gensberg (Frontiers in Neuroscience, 2026)
The comparison of autism spectrum disorder (ASD) and Alzheimer's disease (AD) through shared pathophysiologic features offers intriguing insights into the similarities between the two disease states. The authors suggest diminished cerebrospinal fluid (CSF) drainage through the lymphatic system, perivascular system, and nasal turbinates may occur in ASD and AD, and be an important contributing factor in the occurrence of both disorders. Obstruction of the CSF's normal nasal lymphatic drainage results in abnormal processing of the waste proteins tau and amyloid in the brain in both of these disease states. Reproducible research has shown that ASD and AD patients, when compared to normal controls, exhibit increased extra-axial CSF, enlarged perivascular spaces, magnetic resonance imaging evidence of glymphatic dysfunction, and olfactory dysfunction. Some comparisons between the two disease states are robust while others remain speculative. However, the recognition of overlapping pathophysiologic and genetic features between the two disease states not only furthers understanding of these complex conditions, but could also pave the way for novel therapeutic avenues. The goal of this article is to demonstrate the empirically known similarities between ASD and AD and to stimulate research investigating CSF lymphatic drainage through the nasal turbinates. The authors suggest various ways to confirm their findings and provide suggestions for new therapeutic approaches for these disease states aimed at increasing the movement of CSF originating in the brain through the glymphatic system to meningeal and nasal turbinate lymphatics.